A prolegomenon to the study of Paul - Hart, Patrick (Supplements to Method & Theory in the Study of Religion, 2020)
A Prolegomenon to the Study of Paul examines foundational assumptions that ground all interpretations of the apostle Paul. This examination touches on several topics, invoking issues pertaining to truth, hermeneutics, canonicity, historiography, pseudonymity, literary genres, and authority. Underlying all of this is a guiding thesis, namely, that every encounter with Paul involves "Pauline Archimedean points," or fixed points of reference that establish the measure for constructing any interpretation of Paul whatsoever. Building on this, the author interrogates various issues that inform the formation of these Pauline Archimedean points, in pursuit of an important but modest goal: to urge Pauline readers to engage in a modicum of self-reflection over the various considerations that precondition all of our efforts to comprehend Paul.